Responding to COVID-19: CGIAR's contribution to global response, recovery and resilience - CGIAR System Organization (2020)
The COVID-19 pandemic, itself likely the result of unsustainable food, land and water systems, is exposing weaknesses in food systems, societies and economies around the world. The health risks of the pandemic, combined with the social and economic impacts of measures to stop the spread of the disease (e.g. social isolation directives, travel bans, border closures) are posing threats to food, nutrition and water security, as well as continued progress on global goals to end poverty and hunger, especially in low- and middle-income countries. Without substantial emergency relief, 140 million people could fall into extreme poverty, potentially increasing hunger and malnutrition for millions. Women, youth, migrant workers and poor urban populations are among those most significantly impacted. The global response to the pandemic must be swift and science-based, harnessing new and existing knowledge. Solutions need to be coordinated across sectors to provide immediate response and assistance for those most in need, ongoing and inclusive support in recovery and, perhaps most importantly, future resilience to all shocks–including climate extremes. The COVID-19 crisis presents an unprecedented opportunity for humanity to “build back better,” particularly in the food systems at the root of the pandemic. The crisis has demonstrated how quickly society can fail – but also that collective positive change in human behavior is possible at scale and speed. CGIAR will join its network of partners to co-lead global debate and action on what “building back better” looks like for food, water and land systems.